Investigating Soil Moisture Content and Ph Levels in Eucalyptus Forest: A Case Study of Kabale District South Western Uganda. - Taremwa, Brenan (Kabale University, 2025)
Eucalyptus trees are known for their negative impact on the physio-chemical properties of soils, with particular concerns regarding soil water and pH levels. This study examined the relationship between soil pH and moisture content at varying distances from eucalyptus plantations in Kabale District, southwestern Uganda. Soil samples were collected at distances of 0 meters (within the plantation), 5 meters, 10 meters, 20 meters, and 30 meters from the plantation, with the sampling conducted at a selected site on Kihumuro Hill, east of Kabale Municipality. Soil moisture was determined using the gravimetric method, where fresh soil samples were dried in an oven at 105°C for 8 hours. The difference between the fresh and dry weights was calculated as the moisture content. Soil pH was measured using a pH meter by immersing it in a soil solution and recording the displayed pH value. The findings revealed that soil pH decreased closer to the eucalyptus trees, reaching a pH of 4.9 at 0 meters from the plantation. Similarly, soil moisture content declined as the distance to the eucalyptus trees decreased, dropping from 25% at 30 meters to 2.04% at 0 meters.